(untitled) (Asian Journal of Medical and Biological Research, 2016)
The Effect of lead acetate alone and in combination with whole milk on body weight gain and some biochemical parameters were carried out on a total of 15 (15 days old) male weaning Long- Evans strain rats. The rats were randomly divided into three equal groups, each consisting of five rats. Rats of group A were kept as control (without giving any treatment), group B received lead acetate alone @ 6mg/ml drinking water and group C received lead acetate @ 6mg/ml plus whole milk (Star ship®) 150 mg/ml drinking water. The result showed that body weight gain of control group per week per rat was found to increase but in treated group B, the body weight gain was found to decrease most significantly (P< 0.01) on day 56 while in group C, body weight was reduced significantly (P< 0.05) on day 56. The reducing body weight gain was less in group C than group B. A most significantly (P< 0.01) increased SGOT and SGPT values were observed in Group B but in group C, those count increased significantly (P< 0.05) on day 56 of experiment. From the study it was concluded that treatment with lead acetate at low doses has adverse effects on body growth and liver functions in experimental animals. Asian J. Med. Biol. Res. June 2016, 2(2): 183-189